2004
DOI: 10.1017/s0317167100003644
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of Normal Pituitary Structures in Sellar Pathologies on MRI

Abstract: The use of magnetic resonance imaging (MRI) enhanced the distinction between the normal residual pituitary parenchyma and sellar lesions and even made the differentiation of the neurohypophysis from the adenohypophysis possible.In plain T1-weighted MRI images, the neurohypophysis can be located as the "bright spot" (BS) by its spontaneous hyperintense appearance.1 , 2 Gadopentate-dimeglumine (Gd-D T PA) injection not only increases the sensitivity of the examination by an average of 15%, but also makes it poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…MRI diagnosis value for cases of sellar region lesions has been recognized and MRI has been proved to be the best imaging method to observe pituitary structure and lesions (21). With higher signal-to-noise ratio and tissue contrast, 3.0T MRI can optimize the display of microscopic anatomical structures, improve spatial image resolution thus it is suitable to be used in study of pituitary lesions in children.…”
Section: Discussionmentioning
confidence: 99%
“…MRI diagnosis value for cases of sellar region lesions has been recognized and MRI has been proved to be the best imaging method to observe pituitary structure and lesions (21). With higher signal-to-noise ratio and tissue contrast, 3.0T MRI can optimize the display of microscopic anatomical structures, improve spatial image resolution thus it is suitable to be used in study of pituitary lesions in children.…”
Section: Discussionmentioning
confidence: 99%
“…In all the patients, the axial, sagittal, and coronal series were evaluated, to specifically identify the NRPG including the neurohypophyseal bright spot (BS) and the residual adenohypophysis (RAH) on the pre- and post-gadolinium images, respectively. The maximal diameters in each plane were used to calculate the NRPG volume, which was compared with a database of 102 normal controls,[20] in order to obtain a percentage of the preoperative compression of the NRPG as well as the percent of the postoperative reconstitution. All pre- and postoperative MR images were also evaluated according to the detectability, location, and configuration of the pituitary gland.…”
Section: Methodsmentioning
confidence: 99%
“…4,19,20 Furthermore, localization of the normal gland distorted by sellar pathology often relies on inconsistent findings, such as a hyperintense posterior pituitary. 1,6 Qualitative descriptions only of mass in the pituitary fossa also fail to provide a reproducible guide for preoperative planning and intraoperative manipulation.…”
Section: 15mentioning
confidence: 99%
“…To date, a single study has taken this ap- proach. In a retrospective study, Sade et al 19 identified the normal gland via the "bright spot." They found an overall sensitivity of 58% in their patient population.…”
mentioning
confidence: 99%